« IMPACTS DES MESURES D’ETAT D’URGENCE SANITAIRE DE LA PANDEMIE DU COVID-19 SUR LES DROITS INTANGIBLES EN REPUBLIQUE DEMOCRATIQUE DU CONGO» - NGANDU, Fabien MUTANGALA (IJRDO - Journal of Social Science and Humanities Research, 2022)
The state of health emergency declared in accordance with Ordinance No. 20/014 of March 24, 2020 and by Articles 69, 79, 85, 144 and 145 of the Constitution of February 18, 2006 as amended by Law No. 11/002 of January 20, 2011 revising certain articles of the Constitution of the Democratic Republic of Congo, although supported by that bearing No. 17/024 of July 10, 2017 on the organization and functioning of the Government, methods of collaboration between the President of the Republic and the Government as well as between the members of the Government, especially in its article 62.Measures have been taken to protect the Congolese people and foreign citizens in its area during this period of the COVID-19 pandemic. But they have derogated from the respect of the fundamental rights of the Congolese citizen in accordance with article 61 of the constitution of February 18, 2006 as modified by Law n ° 11/002 of January 20, 2011 revising certain articles of the Constitution of the ground floor.